Determinant of Poverty in Indonesia - Avi Budi Setiawan; Fauzul Adzim (Economics Development Analysis Journal, 2017)
This research aims at knowing the relationship between the labor force participation level, the average of expenditure per capita, the literacy level, and the capital investment and the poverty level in Indonesia at 2014. The secondary data in this research were obtained from the Central Bureau of Statistics (BPS) and the National Population and Family Planning Bureau (BKKBN) in 32 provinces in Indonesia (cross section). The method of research used is Ordinary Least Square Method with level of confidence of 95%. The research result shows that the average of expenditure per capita and the capital lending have a significant influence on the poverty level in 2014, while the labor force participation level and the literacy level have no significant influence on the poverty.